The General Election Commission (KPU) Communication Model in Increasing Voter Participation in the Election of the Governor of Sumut 2018 in Labuhanbatu Selatan District - Sarino Sarino; Erwan Efendi; Anang Anas Azhar (Budapest International Research and Critics University, 2021)
This study aims to find out The General Election Commission (KPU) Communication Model in Increasing Voter Participation in the Election of the Governor of Sumut 2018. This research is included in qualitative research. Qualitative research is a social research which fundamentally relies on observing humans in their own domain and relating to those people who seek toreveal actual facts / phenomena that occur in the field. Based on the results of research that has been carried out with the title